1974
DOI: 10.2307/1959952
|View full text |Cite
|
Sign up to set email alerts
|

Political Implications of Gender Roles: A Review of the Literature

Abstract: This essay introduces the reader to the contemporary literature on gender roles and feminine behavior, including the major concepts, empirical findings, and social thought which have implications for political behavior and research. Gender roles as they relate to the psychology and activity of men and women, and their systemic cultural, economic, and legal ramifications provide an explanation and a basis for understanding political behavior, including recurrent women's protest movements. Contemporary writing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…time, money, and civic skills, which are usually the product of an elevated socio-economic status. It has been long argued that women's resources, in particular their level of education and income, explained their lower levels of political participation (Ballmer-Cao 1978;Krauss 1974;Randall 1987;Welch 1977). This widely used explanation continues to be applied to various aspects of political participation (Schlozman et al 1994).…”
Section: Resourcesmentioning
confidence: 99%
“…time, money, and civic skills, which are usually the product of an elevated socio-economic status. It has been long argued that women's resources, in particular their level of education and income, explained their lower levels of political participation (Ballmer-Cao 1978;Krauss 1974;Randall 1987;Welch 1977). This widely used explanation continues to be applied to various aspects of political participation (Schlozman et al 1994).…”
Section: Resourcesmentioning
confidence: 99%
“…Reviews of gender-related research (Bourque and Grossholtz 1974;Jaquette 1974Jaquette , 1976Kraus 1974;Boals 1975; Goot and Reid 1975;Shanley and Schuck 1975;Carroll 1979;Githens 1983Githens , 1984 are remarkably similar in their critique of the use of male criteria to evaulate women's role in politics.…”
Section: Women's Studies and Gender-related Researchmentioning
confidence: 99%
“…Hora and Lynn [1974] found that mothers displayed less political efficacy than nonmothers and that differences increased among women of higher social status. Since women have traditionally defined their stake in the community to be closely associated with their primary roles as wives and mothers, they have frequently defined their interest in the poh'tical system in terms of the educational process and social welfare-medical services, services for the elderly-as well as "cultural" activities [Boyd, 1968;Krauss, 1974;Karnig and Walter, 1976]. Socialization into limited roles seems an important factor in self-elimination of women from many types of political 46 Stuart and van Es activity.…”
Section: Community Structure and Political Leadersmentioning
confidence: 99%
“…Using their data, they contrast "the public office versus intraparty career styles" and the "selfserving (public office, power and influence) versus public-serving (concern for the party, its candidates and its program)" motivations of men and women as reflective of sex-role differences similar to those of family roles. The "expressive" or supportive functions of women, which reflect 48 Stuart and van Es traditional sex-role ideology, are as pervasive in political party activities as in other areas of men's and women's life styles [Boyd, 1968;Millet, 1969;Costantini and Craik, 1972;Krauss, 1974].…”
Section: Community Structure and Political Leadersmentioning
confidence: 99%
See 1 more Smart Citation